2021
DOI: 10.3389/fpsyg.2021.741735
|View full text |Cite|
|
Sign up to set email alerts
|

Are Family Physical Activity Habits Passed on to Their Children?

Abstract: Studies of the familial association of physical activity (PA) and sedentary behavior (SB) have increased in recent years. However, there is a lack of studies that have objectively examined the correlates between parents, grandparents, and childrens' PA. Therefore, the purpose of this study was to measure PA using accelerometers to determine the extent to which PA and SB correlate among parents, grandparents, and children. A sample of 169 children between 11–14 years (77 boys and 97 girls), 225 parents (98 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Parents may help motivate their children, which can significantly influence engagement in health-promoting behaviour, for example, PA. The findings from a recent study in Slovenia among primary school children and their parents showed that mothers' moderate-vigorous PA was significantly associated with children's moderate to vigorous-intensity PA (Zovko et al 2021). Self-determination theory applied among US school adolescents showed that both identified regulation and intrinsic motivation were positively associated with moderate to vigorous-intensity PA (Nogg et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Parents may help motivate their children, which can significantly influence engagement in health-promoting behaviour, for example, PA. The findings from a recent study in Slovenia among primary school children and their parents showed that mothers' moderate-vigorous PA was significantly associated with children's moderate to vigorous-intensity PA (Zovko et al 2021). Self-determination theory applied among US school adolescents showed that both identified regulation and intrinsic motivation were positively associated with moderate to vigorous-intensity PA (Nogg et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Families provide the foundation for learning and adopting health behaviors (Hunt et al, 2015 ). Extensive research has demonstrated the impact of the family environment on the formation of exercise habits among adolescents (Mota, 1998 ; Zovko et al, 2021 ). For example, factor such as family support (Kuo et al, 2007 ; Álvarez Muñoz and Hernández Prados, 2023 ; Hu and Cai, 2023 ), parental role modeling (Adkins et al, 2017 ; Do et al, 2023 ), and the availability of resources and opportunities for physical activity within the family context (Álvarez Muñoz and Hernández Prados, 2023 ) have been found to be crucial in influencing adolescents' exercise behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, children who were inactive, although non-sedentary, followed less healthy dietary patterns with a higher likelihood of belonging to single-parent families. Indeed, research showed that single-parent families had children who exhibited poorer dietary habits [ 25 ] and were prone to sedentariness [ 26 ], likely because parents’ involvement in physical activities plays a significant role in children’s physical activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%